Unbiased Screening Identifies Functional Differences in NK Cells After Early Life Psychosocial Stress - Fernandes, Sara B.; Patil, Neha D.; Meriaux, Sophie; Theresine, Maud; Muller, Claude. P.; Leenen, Fleur A. D.; Elwenspoek, Martha M. C.; Zimmer, Jacques; Turner, Jonathan D. (Frontiers in Immunology, 2021)
Early Life Adversity (ELA) is closely associated with the risk for developing diseases later in life, such as autoimmune diseases, type-2 diabetes and cardiovascular diseases. In humans, early parental separation, physical and sexual abuse or low social-economic status during childhood are known to have great impact on brain development, in the hormonal system and immune responses. Maternal deprivation (MD), the closest animal model available to the human situation, is known to similarly induce long lasting behavioural effects, to cause changes in the HPA axis and to have an impact in the immune system. Even though the immune responses to potential pathogens after early stress have been somehow documented, the mechanisms by which they occur are still not fully understood. Here, we have demonstrated that maternal separation, in both humans and rats, significantly affects the sensitivity of the immune system in adulthood. Particularly, NK cells’ profile and response to target cell lines are significantly changed after childhood adversity. These immune cells in rats are not only less cytotoxic towards YAC-1 cells, but also show a clear increase in the expression of maturation markers after 3h of maternal separation. Similarly, individuals who suffered from ELA display significant changes in the cytotoxic profile of NK cells together with decreased degranulation capacity. Altogether, these results lead us to conclude that one of the key mechanisms by which the immune system becomes impaired after ELA might be due to a shift on the senescent state of the cells, specifically NK cells. Elucidation of such a mechanism highlights the importance of ELA prevention and how NK targeted immunotherapy might help attenuating ELA consequences.